Effect of nutrition improvement program implementation on stunting in children under two years old - Yolanda Handayani; Martya Rahmaniati Makful (Berita Kedokteran Masyarakat (BKM), 2019)
PurposeThe first thousand days of life is a critical momentum where children from the age of 2 years need the best nutrition for brain development. This study examined the effect of appropriate timing of supplementary feeding and vitamin A consumption on nutritional status of children below age of twoMethodThe design of this study is cross sectional. The sample in this study is based on data of the Nutritional Status Monitoring 2017 which is amounted to 27.208, consisting of pregnant women who took iron folate supplementation (TTD); mother gave early breastfeeding initiation, exclusive breastfeeding, and supplementary food; children who received vitamin A; and children who get height measurement by age.ResultsThe odds of mothers not providing supplementary feeding to children aged 7-23 months have a short nutritional status 1,137 times greater than mothers who provide supplementary feeding. While the Vitamin A variable has odds ratio 0,659 significantly, the odds of children not getting Vitamin A have short nutritional status 0, 659 times greater than children who received Vitamin A. Conclusion: The risk of stunting occurs in a period of 6 to 24 months due to the period for growth in height. Health workers at the primary health care should inform mothers to provide supplementary food and vitamin A at the 6-24 month of age.